PENGUKURAN KINERJA SUPPLY CHAIN MANAGEMENT PERGURUAN TINGGI MENGUNAKAN METODE AHP-SCOR - Andries Anwar (Universitas Mercu Buana, 2018)
Competition in the education industry is becoming a major challenge for the University in carrying out activities of educational services. The University sued for creative thinking in implementing the strategy of competing to produce a higher quality education services, starting with the screening of students up to the graduates received industrial market. Universities need to do engineering management by applying the concept of supply chain management or supply chain management (SCM). The purpose of this research is to analyze the proposed framework performance SCM Bina Darma University by using the method of AHP-SCOR. Determination of the proposed Key Performance Indicator (KPI)), which became a benchmark in performance measurement involves three stakeholders universities namely the University organization, supplier, and customer interests on the flow of the SCM. The method of Analytical Hierarchy Process (AHP) and SCOR is used to assist in determining priority criteria SCM University. The results of the identification and measurement of the values obtained with the model of SCOR for each process performance as follows: plan valued at 2.64, source of value worth 4.69 4.04, make, and deliver valued at 11.82. The total value of SCOR for universities was 23.19, prioritized improvement on performance with the smallest value i.e. the process Plan with a value of 2.64.